385 POTENTIAL MALE CONTRACEPTIVE TARGET: GERM CELL-SPECIFIC VASA PROTEIN LOCALIZATION IN MONKEY AND HUMAN TESTES. Issue 1 (1st January 2007) - Ma, K.; Berglund, F.; Crespo, M.; Lue, Y. H.; Swerdloff, R. S.; Sinha Hikim, A. P.; Liu, Y. X.; Cui, Y. G.; Wang, X. H.; Sha, J. H.; Zhou, Z. M.; Wang, C.
Abstract : We previously demonstrated that pachytene and diplotene spermatocytes and round spermatids are the most susceptible cells to undergo apoptosis in response to either a withdrawal of intratesticular testosterone, increased testicular temperature, or a combination of both in rats and monkeys. Our study focuses on vasa (DDX4 or MvH), a specific meiotic and/or postmeiotic molecule essential for germ cell survival and development. Vasa is a member of the DEAD (Asp-Glu-Ala-Asp) box family of ATP-dependent RNA helicases and participates in RNA unwinding, translation initiation, and RNA turnover. Previously, the vasa gene was found to be conserved across species in Caenorhabditis elegans, Xenopus, zebra fish, mice, and rats. In mice, vasa protein has been localized in spermatocytes and round spermatids and vasa knockout mice were infertile due to an arrest of spermatogenesis at zygotene spermatocytes. The objective of this study is to compare vasa protein expression and localization in rat, monkey, and human testes. Testicular samples were obtained from groups of four adult rats, four adult monkeys, and four fertile men. Bouin's fixed, paraffin-embedded testicular sections were used for vasa immunohistochemistry. Vasa proteins were predominantly localized in the cytoplasm of pachytene and diplotene spermatocytes and round spermatids across all three species. The vasa proteins were condensed in the chromatoid bodies of late spermatocytes and round spermatids. Our studies also confirm vasa as an evolutionary conserved germ cell-specific molecule since vasa proteins were present in rat, monkey, and human testes. The function of vasa will be determined in the monkey and human testes after interventions to regulate spermatogenesis. Further investigation of vasa in the human testes may lead to a potential target for male contraception.